(untitled) (Philological Studies, 2019)
The article deals with moral realism, intuitionism and moral phenomenology. It consists of three main sections. In the first section I define moral realism and moral intuitionism. The second section deals with moral phenomenology and introduces the notion of phenomenological argument. The last section deals with phenomenological arguments supporting moral realism and intuitionism (moral cognitivism, internalism about motivation, moral pluralism).